2010
DOI: 10.1007/s00268-010-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Tc99m‐MIBI‐SPECT Imaging Scans in Persistent Primary Hyperparathyroidism

Abstract: BackgroundIn primary hyperparathyroidism (PHPT) the predictive value of technetium 99m sestamibi single emission computed tomography (Tc99m-MIBI-SPECT) for localizing pathological parathyroid glands before a first parathyroidectomy (PTx) is 83–100%. Data are scarce in patients undergoing reoperative parathyroidectomy for persistent hyperparathyroidism. The aim of the present study was to determine the value of Tc99m-MIBI-SPECT in localizing residual hyperactive parathyroid tissue in patients with persistent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
3
26
0
2
Order By: Relevance
“…Moreover, these limitations also apply to MIBI-SPECT as seen in our cohort and as demonstrated by other authors with sensitivities of 67-86 % [13][14][15][16]. In addition, the diagnostic work-up is impeded in patients with concomitant nodular goiter, which is endemic in the German population [17,18].…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, these limitations also apply to MIBI-SPECT as seen in our cohort and as demonstrated by other authors with sensitivities of 67-86 % [13][14][15][16]. In addition, the diagnostic work-up is impeded in patients with concomitant nodular goiter, which is endemic in the German population [17,18].…”
Section: Discussionmentioning
confidence: 62%
“…In a retrospective study, Witteveen et al (19) reported that 99m Tc-sestamibi SPECT imaging was of limited value in the reoperative setting of hyperparathyroidism in 19 consecutive patients, as compared with the performance of 99m Tc-sestamibi SPECT in 23 control patients with sporadic hyperparathyroidism due to single-gland disease who underwent scanning before initial surgery. Thus, good performance of a technique before primary operation does not necessarily ensure good performance also in the reoperative setting.…”
Section: Discussionmentioning
confidence: 99%
“…As initially described, the first imaging study is usually US, together with nuclear medicine imaging. However, in patients with persistent PHPT, the 99m Tc-MIBI sensitivity has been show to decline from 80%, before initial surgery, to 50% (12,31). If localization is not obtained with US and 99m Tc-MIBI scan, additional imaging studies should be performed.…”
Section: Availability Of Rapid Pth Assaymentioning
confidence: 99%